Geomechanical Characterization of the Rock Mass along a Deep Vertical Borehole - Maria Clorinda Mandaglio (Geotechnics, 2024)
Deep vertical boreholes play a crucial role in underground exploration, resource extraction such as geothermal energy extraction, oil and gas exploration, underground waste storage and various underground engineering applications. The geomechanical properties of the rocks surrounding these boreholes are essential for designing safe, efficient drilling operations, for using adequate technologies and equipment and for providing mitigation measurements. Specifically, when the excavations are performed inside in-depth, extremely fractured and weathered rocks, the identification of zones more susceptible to crossing is a primary goal. This paper presents a thorough investigation into the rock masses surrounding a deep vertical borehole that involved the collection of core samples from the deep vertical borehole, laboratory testing, in situ tests and the application of geomechanical models to characterize the crossed rock masses. After a lithological and structural description of the rock masses and a description of the methodology used for their characterization, this paper focuses on the geomechanical parameterization of the rock mass using the uniaxial compressive strength of the intact rock (σci) and the Geological Strength Index (GSI). The obtained findings highlight the extreme variability in the depth of the geomechanical parameters of crossed rocks, which decreased with the depth. This methodology can be used to characterize rock masses along other deep boreholes, for which there is a lack of research, and to define the most problematic zones for underground crossing where different support works must be designed.